2001
DOI: 10.2176/nmc.41.599
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of Pial Arteriovenous Malformation Associated With Early Thrombosis of the Draining System Following Stereotactic Radiosurgery. Case Report.

Abstract: A 50-year-old man was treated with stereotactic gamma knife radiosurgery for an incidentally detected small callosal arteriovenous malformation (AVM) with stenosis of the main draining pathway. He suffered two episodes of intraventricular hemorrhage at 4 and 14 weeks after the radiosurgery. Radiological studies demonstrated that the anterior portion of the draining system including a varix, which had been irradiated, was thrombosed before the obliteration of arteriovenous shunts. Stereotactic radiosurgery is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…(DOI: 10.3171/2009.1.JNS08784) hemorrhage within 72 hours of SRS. 64 There have been a few more documented cases of AVM hemorrhage within 4-30 days after SRS; 6,12,[76][77][78]96,99 with the exception of data in a case of AVM rupture 29 days post-SRS, 77 the clinical and radiographic details of the remaining cases are not known.…”
Section: Radiology University Of Washington Seattle Washingtonmentioning
confidence: 99%
“…(DOI: 10.3171/2009.1.JNS08784) hemorrhage within 72 hours of SRS. 64 There have been a few more documented cases of AVM hemorrhage within 4-30 days after SRS; 6,12,[76][77][78]96,99 with the exception of data in a case of AVM rupture 29 days post-SRS, 77 the clinical and radiographic details of the remaining cases are not known.…”
Section: Radiology University Of Washington Seattle Washingtonmentioning
confidence: 99%
“…Although our patient had an asymptomatic bleed, authors have documented hemorrhage after GKRS caused by early draining vein occlusion previously. 12 Early draining vein occlusion has been postulated to be one of the causes of postradiosurgery hemorrhage. 1 The occurrence of early draining vein occlusion was influenced by preexisting varix, venous stasis, and turbulent flow.…”
Section: Discussionmentioning
confidence: 99%
“…(Nataf et al 2004) Within 4 to 30 days following SRS there are a few more documented cases of post-radiosurgery AVM hemorrhage. (Chang et al 2004;Colombo et al 1994;Pollock et al 1994;Shimizu et al 2001;Shin et al 2004;Yen et al 2007;Zabel-du Bois et al 2007;Celix et al 2009) With two exceptions, the cases reported in the literature of AVM hemorrhage in the early period following radiosurgery are presented in the context of retrospective observational cohort studies and the clinical and radiographical details of the cases are not described. One published case report of rupture of a pial AVM 29 days following SRS was associated with pretreatment partial thrombosis of a distal draining vein varix.…”
mentioning
confidence: 99%
“…One published case report of rupture of a pial AVM 29 days following SRS was associated with pretreatment partial thrombosis of a distal draining vein varix. (Shimizu et al 2001) The authors of this chapter recently published a case of AVM hemorrhage occurring 9 days after gamma knife radiosurgery, with radiographic documentation of venous thrombus formation immediately preceding intracranial hemorrhage. (Celix et al 2009) We posit that the pathophysiology of AVM rupture in the early period following SRS differs from rupture occurring months after radiosurgery.…”
mentioning
confidence: 99%